শহীদ জননী জাহানারা ইমাম স্বারকগ্রন্থ - Riṭana, Lut̲phara Rahamāna (ঢাকা : সাস পাবলিকেশন্স : Ekamātra paribeśaka Pratīka Prakāśana Saṃsthā, 1995)
Commemorative volume on Jāhānāra Imāma, woman political activist from Bangladesh; comprises articles, poems, and sketches on her life and activities.
In Bengali.
Keywords: ইমাম, জাহানারা.; Women politicians -- Bangladesh -- Biography; Bangladesh -- Politics and government -- 1971-